Reading Twitter's mode of operation through lacan: the experience of the real in social media age - Semercioğlu, Halit Can (İstanbul Bilgi Üniversitesi, 2017)
[Abstract Not Available]
Twitter'in işleyiş biçimini lacan üzerinden okumak: sosyal medya çağında gerçek deneyimi